Sciatic nerve fractional anisotropy and neurofilament light chain protein are related to sensorimotor deficit of the upper and lower limbs in patients with type 2 diabetes - Kender, Zoltan; Jende, Johann M. E.; Kurz, Felix T.; Tsilingiris, Dimitrios; Schimpfle, Lukas; Sulaj, Alba; von Rauchhaupt, Ekaterina; Bartl, Hannelore; Mooshage, Christoph; Göpfert, Jens; Nawroth, Peter; Herzig, Stephan; et al. (Frontiers in Endocrinology, 2023)
Background: Diabetic sensorimotor polyneuropathy (DSPN) is one of the most prevalent and poorly understood diabetic microvascular complications. Recent studies have found that fractional anisotropy (FA), a marker for microstructural nerve integrity, is a sensitive parameter for the structural and functional nerve damage in DSPN. The aim of this study was to investigate the significance of proximal sciatic nerve’s FA on different distal nerve fiber deficits of the upper and lower limbs and its correlation with the neuroaxonal biomarker, neurofilament light chain protein (NfL). Materials and methods: Sixty-nine patients with type 2 diabetes (T2DM) and 30 healthy controls underwent detailed clinical and electrophysiological assessments, complete quantitative sensory testing (QST), and diffusion-weighted magnetic resonance neurography of the sciatic nerve. NfL was measured in the serum of healthy controls and patients with T2DM. Multivariate models were used to adjust for confounders of microvascular damage. Results: Patients with DSPN showed a 17% lower sciatic microstructural integrity compared to healthy controls (p<0.001). FA correlated with tibial and peroneal motor nerve conduction velocity (NCV) (r=0.6; p<0.001 and r=0.6; p<0.001) and sural sensory NCV (r=0.50; p<0.001). Participants with reduced sciatic nerve´s FA showed a loss of function of mechanical and thermal sensation of upper (r=0.3; p<0.01 and r=0.3; p<0.01) and lower (r=0.5; p<0.001 and r=0.3; p=<0.01) limbs and reduced functional performance of upper limbs (Purdue Pegboard Test for dominant hand; r=0.4; p<0.001). Increased levels of NfL and urinary albumin-creatinine ratio (ACR) were associated with loss of sciatic nerve´s FA (r=-0.5; p<0.001 and r= -0.3, p= 0.001). Of note, there was no correlation between sciatic FA and neuropathic symptoms or pain. Conclusion: This is the first study showing that microstructural nerve integrity is associated with damage of different nerve fiber types and a neuroaxonal biomarker in DSPN. Furthermore, these findings show that proximal nerve damage is related to distal nerve function even before clinical symptoms occur. The microstructure of the proximal sciatic nerve and is also associated with functional nerve fiber deficits of the upper and lower limbs, suggesting that diabetic neuropathy involves structural changes of peripheral nerves of upper limbs too.